Metacognitive Awareness And Perceived Use Of Reading Strategies In Academic Reading Comprehension: Case Of Algerian Efl Students - Cherik, Louiza; Aliouchouche, Fadhila (جامعة الوادي - university of Eloued, 2022)
students when reading academic materials. Participants were 220 second year undergraduate students from the department of English as a Foreign Language at Mouloud Mammeri University. They completed a 15- item survey of metacognitive reading strategies (MARSI) aimed at describing their reading strategies use when dealing with academic reading comprehension. Statistical Package for social sciences was used to determine the frequency and type of strategies employed by the participants. The results revealed that students’ level of awareness of reading strategies is in the medium range. It also demonstrated a predominant use of support reading strategies and a lower frequency use of problem solving strategies and global reading strategies. Implications for students’ instruction, in reading strategies to raise their awareness and to achieve reading comprehension are suggested.
Article
Keywords: English as a Foreign Language ; Metacognitive Awareness ; Reading Comprehension ; Reading Strategies